CLUSTER STRUCTURES AND THEIR APPLICATIONS IN DATA MINING - V. V. Krasnoproshin; V. G. Rodchanka (Informatika)
A notion of cluster structures is introduced. These structures can be used to identify and present the hidden knowledge" in data mining. It demonstrates the use of cluster structures to address automatic pattern recognition with training.